Análisis, diseño e implementación de un sistema multimedia educativo enfocado a incrementar las habilidades numéricas y lingüísticas en niños con Síndrome de Down del nivel primaria aplicando la metodología Brian Blum para el Instituto Fiscal de Educación especial de El Oro de la ciudad de Machala - Cruz Alvarado, Diego Fernando (2014)
The Public Institute of Special Education of El Oro city of Machala is responsible for training children with special needs, this means that education is taught by teachers who are trained for this type of problem but not always have the necessary tools to help students to reinforce learning.